Acute hormonal, immunological and enzymatic responses to a basketball game - Denis Foschini; Jonato Prestes; Richard Diego Leite; Gerson dos Santos Leite; Felipe Fedrizzi Donatto; Christiano Bertoldo Urtado; Bianca Trovello Ramallo (Universidade Federal de Santa Catarina, 2008)
The objective of the present study was to analyze the acute hormonal, immunological and enzymatic responses of professional basketball players to a basketball game. The sample was composed of eight basketball athletes, with a minimum of 4 years' experience in basketball. A real game was simulated with a total duration of 40 minutes, divided into two halves of 20 minutes each and an interval of 10 minutes between halves. Blood samples were collected before and immediately after the game (20 ml, vacuum tube system). The variables analyzed were: testosterone and cortisol hormones, total leukocytes, neutrophils, lymphocytes, monocytes and the enzymes creatine kinase (CK) and lactate dehydrogenase (LDH). Statistical analysis was with descriptive statistics and the Student's t test for paired samples to p≤0.05. The pre (13.34 nmol/L and 301.97 nmol/L) and post game (17.34 nmol/L and 395.91 nmol/L) levels of testosterone and cortisol were statistically different, with higher levels after the game for both hormones. The immune cell counts exhibited significant differences for total leukocytes (6393.75 nmol/L and 9158.75 nmol/L) and neutrophils (3532.5 nmol/L and 6392.62 nmol/L), with levels being higher after the game. No statistical differences were observed for the enzymatic variables. Therefore, based on the markers analyzed, testosterone and cortisol exhibited pronounced increases after the game and the same behavior was observed for total leukocytes and neutrophils.